Fast Dynamic Synthesis of MIL-68(In) Thin Films in High Optical Quality for Optical Cavity Sensing - Monjezi, Bahram Hosseini; Okur, Salih; Limbach, Rene; Chandresh, Abhinav; Sen, Kaushik; Hashem, Tawheed; Schwotzer, Matthias; Wondraczek, Lothar; Woell, Christof; Knebel, Alexander (ACS nano, 2023)
Fabrication of metal-organic framework (MOF) thin films rigidly anchored on suitable substrates is a crucial prerequisite for the integration of these porous hybrid materials into electronic and optical devices. Thus, far, the structural variety for MOF thin films available through layer-by-layer deposition was limited, as the preparation of those surface-anchored metal-organic frameworks (SURMOFs) has several requirements: mild conditions, low temperatures, day-long reaction times, and nonaggressive solvents. We herein present a fast method for the preparation of the MIL SURMOF on Au-surfaces under rather harsh conditions: Using a dynamic layer-by-layer synthesis for MIL-68(In), thin films of adjustable thickness between 50 and 2000 nm could be deposited within only 60 min. The MIL-68(In) thin film growth was monitored in situ using a quartz crystal microbalance. In-plane X-ray diffraction revealed oriented MIL-68(In) growth with the pore-channels of this interesting MOF aligned parallel to the support. Scanning electron microscopy data demonstrated an extraordinarily low roughness of the MIL-68(In) thin films. Mechanical properties and lateral homogeneity of the layer were probed through nanoindentation. These thin films showed extremely high optical quality. By applying a poly(methyl methacrylate) layer and further depositing an Au-mirror to the top, a MOF optical cavity was fabricated that can be used as a Fabry-Perot interferometer. The MIL-68(In)-based cavity showed a series of sharp resonances in the ultraviolet-visible regime. Changes in the refractive index of MIL-68(In) caused by exposure to volatile compounds led to pronounced position shifts of the resonances. Thus, these cavities are well suited to be used as optical read-out sensors.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Metal−Organic Frameworks; MOF Gas Sensor; Optical Quality SURMOF; Resonating Cavity; Thin Film Deposition